2015
DOI: 10.1186/s12906-015-0919-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phenolic composition on hepatoprotective and antioxidant effects of four desert medicinal plants

Abstract: BackgroundFlavonoids and other polyphenols play a protective role in liver diseases and possess a high antioxidant capacity.ObjectiveTo compare and evaluate the antioxidant and hepatotoprotective activities of 4 deserts plants, Fagonia indica Burm. f., Calotropis procera R.Br., Zygophylum hamiense Schweinf. and Salsola imbricata Forssk. in correlation to their composition especially their phenolic content.MethodsThe influence of extracting solvent on total phenolic and flavonoidal contents was assessed spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 54 publications
9
47
0
Order By: Relevance
“…This reversal of the enzyme levels by the extract is probably because of their membrane stabilizing activity which prevents leakage of intracellular enzymes. This is in accordance with the generally established view that serum levels of transaminases restored to normal with the regeneration of liver cells and healing of liver parenchyma [19, 50]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This reversal of the enzyme levels by the extract is probably because of their membrane stabilizing activity which prevents leakage of intracellular enzymes. This is in accordance with the generally established view that serum levels of transaminases restored to normal with the regeneration of liver cells and healing of liver parenchyma [19, 50]. …”
Section: Discussionsupporting
confidence: 91%
“…Pareek et al [18] investigated the i n vitro and in vivo antioxidant activity of F. schweinfurthi through DPPH, ABTS radicals and hydrogen peroxide methods and hepatoprotective potential against CCl 4 induced toxicity in HepG2 cells and in rat. Hepatoprotective activity of F. indica has also been reported in earlier studies [19, 20]. Antitumor potential of F. cretica has been reported in different studies [21, 22].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Alzheimer's disease and brain diseases with deficiency in cholinergic function Z. coccienium 9,26 Egypt, Kuwait, Saudi Arabia Gout, Rheumatic pain and hypertension Z. cornutum 10 Algeria Diabetes, hypertension and dermatitis Z. decumbens 27 Egypt, Syria, Sudan Hypotension, fever and GIT spasm Z. dumosum 23,28,29 Egypt Rheumatism, gout, asthma and hypertension Z. fabago 19 China, Spain, Turkey, Iran, Kazakhstan and Iraq Fungal infections, Parasitic worms, constipation, product cough, inflammation, and asthma Z. gaetulum 11 Morocco GIT spasms, hyperglycemia accompanying diabetes and eczema Z. geslini 12 Algeria Hyperglycemia accompanying diabetes Z. hamiense 30 Deserts of Asia and Africa As hepato-protective Z. macropodum 31 China Pain and inflammation Z. melongena 20 Mongolia Snake poisoning (as it inhibits of the snake venom phosphodiesterase)…”
Section: Pakistanmentioning
confidence: 99%
“…Investigations revealed that leaf extracts also contain saponins, tannins, triterpenoids, steroids, glycosides, and flavonoids. The antioxidant and hepatoprotective potentials of flavonoids (Shehab, Abu-Gharbieh, & Bayoumi, 2015) and triterpenoids are well identified. On the other hand, SOD and glutathione peroxidase were increased in fat suspension steatohepatitis model of rat.…”
Section: G Glabra (Licorice)mentioning
confidence: 99%